Soil productivity from the sandy pampas region under the present agricultural conditions - Díaz-Zorita, Martín (Agrociencia Uruguay, 2012)
During the last decade, major changes in the organization, extension and intensifi cation of the agricultural systems from the sandy pampas region are observed. Crop production is mostly performed under continuous zero tillage and with the application of fertilizers. In this region, strong relationships between crop yields and soil properties, mostly related to water and nutrient storage, have been described. The purpose of this presentation is to discuss, supported by specifi c local long-term fi eld trials, about several of the changes in the productivity of the soils of the region under the present management practices. Soil organic matter levels decrease under continuous tillage practices after systems with pastures. But, the application of zero tillage practices contributed to maintain the original soil productivity properties. Production systems established on degraded soils frequently show less water use effi ciency, mainly when are cropped with maize (Zea mays L.). The establishment of continuous fertilization programs based on the suffi ciency for low mobility nutrients (e.g. Phosphorus) shows reduction in the soil extractable levels of the nutrient and lower mean crop production compared with maintenance fertilization programs. The use of winter cover crops in soybean [Glycine max (L.) Merrill] monoculture enhances physical soil properties without benefi ts on crop yields. The crop and soil management practices widely performed during this period have contributed to the soil conservation and to the water use effi ciency. However, the application of suffi ciency fertilization programs could conduct to the reduction in the levels of soil extractable nutrients and in crop productivity. The present agricultural land use in the region requires to intensify in the use of indexes for the diagnosis of soils productivity independently of the actual relationships with today`s yields. The delimitation of homogeneous areas for the application of effi cient soil management practices is needed for the conservation and enhancement of soils productivity capability.